2018
DOI: 10.1186/s12934-018-0901-3
|View full text |Cite
|
Sign up to set email alerts
|

Signal peptides for recombinant protein secretion in bacterial expression systems

Abstract: The secretion of biotechnologically or pharmaceutically relevant recombinant proteins into the culture supernatant of a bacterial expression host greatly facilitates their downstream processing and significantly reduces the production costs. The first step during the secretion of a desired target protein into the growth medium is its transport across the cytoplasmic membrane. In bacteria, two major export pathways, the general secretion or Sec pathway and the twin-arginine translocation or Tat pathway, exist f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
180
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(184 citation statements)
references
References 81 publications
2
180
1
1
Order By: Relevance
“…7B, lane 4). The expression of the C-terminal truncation mutant, dsbA(ss)-ExbD(4458)-His6X was undetectable (data not shown). Because dsbA(ss)-ExbD(49-63) was expressed similarly to the parent peptide but was significantly less inhibitory, it suggested that the first five residues of the dsbA(ss)-ExbD(44-63) peptide were important to inhibit TonB system activity.…”
Section: Resultsmentioning
confidence: 94%
“…7B, lane 4). The expression of the C-terminal truncation mutant, dsbA(ss)-ExbD(4458)-His6X was undetectable (data not shown). Because dsbA(ss)-ExbD(49-63) was expressed similarly to the parent peptide but was significantly less inhibitory, it suggested that the first five residues of the dsbA(ss)-ExbD(44-63) peptide were important to inhibit TonB system activity.…”
Section: Resultsmentioning
confidence: 94%
“…Another important finding here is the observation that translocation is one of the mechanisms for gene compatibility. To date, a general trend in the MBL signal peptide sequence has been identified for each translocation system (e.g., the Sec protein translocation pathway) (46)(47)(48)(49)(50), however, we have little understanding of the relationship between the signal peptide sequence and its translocation efficacy, let alone the incompatibility between the translocation system of a particular organism and the signal peptide sequence of a particular gene. Indeed, the signal peptide is the most variable region in the MBL sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The first 26 residues of VIM-2 has been identified as the signal peptide 14,15,52 , which is a sequence used to translocate the enzyme to the periplasm, then cleaved after transport [53][54][55][56] . Our DMS data supports the known length of the signal peptide as mutations to Cys are much less deleterious before residue 26, suggesting these positions are not incorporated into the mature enzyme in the periplasm.…”
Section: Codon and Amino Acid Optimization In The Signal Peptidementioning
confidence: 99%
“…with 1 or more positive residues, a hydrophobic (H) region (residues 8-21) and a carboxy terminal (C) region (residues 22-26) that precedes the cleavage site containing a PXAXS motif ( Fig. 5a) [53][54][55][56] . The signal peptide is conserved at 17 of 25 positions across all VIM variants, and the remaining are binary differences between the conserved sequences of the VIM-1 and VIM-2 clades ( Fig.…”
Section: Codon and Amino Acid Optimization In The Signal Peptidementioning
confidence: 99%